Study on Thermal Conductivity of Thermal Insulation Cement in Geothermal Well - Zhang, Fengyan; Li, Lixin (Frontiers in Earth Science, 2022)
When geothermal fluids flow to the wellhead along the wellbore, thermal transferred from the high-temperature geothermal fluids to the low-temperature formation, attributing the fact that the temperature of fluids is always higher than the formations at the same depth. This can further lead to the decrease of the fluids’ wellhead temperature and loss of thermal energy. Despite the idea that reducing the thermal conductivity of cement could validly cut down the heat loss of thermal fluids had been mentioned, but there were relatively few specific studies. In this research, we conducted detailed studies on the influencing factors of cement thermal conductivity and compressive strength. The results showed that with the increase of water-cement ratio and insulation materials, thermal conductivity and compressive strength of cement declined clearly. What’s more, curing temperature was also an important factor to improve cement thermal insulation effect, but the testing temperature was opposite. Based on the results, floating beads and expanded perlite could be identified as high-efficiency insulation materials mainly by reducing the volume and heat transfer capacity of cement skeleton. This research provided theoretical guidance for increasing the wellhead temperature of geothermal fluids through insulation cement, and will further enhance the utilized efficiency of geothermal energy.